PROFESSIONAL STATUS OF MEN IN NURSING - Tanya Paskaleva (Peytchinski Publishing, 2020)
Introduction: The modern image of the profession of the "nurse" largely depends on public opinion and attitude. The new era imposes a new concept and a new vision for this profession that is not subject to gender stereotypes and prejudices. Objective: To investigate and analyze the public viewpoint and attitude towards men who practice the nursing profession and to inspect the motivation and professional satisfaction of men practising the profession. Materials and methods: An anonymous survey was conducted among two groups of respondents: 112 people from different age groups and 25 male trainees and practitioners of the nursing profession. The study was conducted within the period from February to March 2019. The collected primary information was introduced and processed with the statistical package SPSS Statistics 16.0. Results: The analysis of the data from the students' admission procedure in two universities for five consecutive years shows the insufficient interest of men in the nursing profession. The main reasons are: firstly, the name of the profession - 47,3%; the lowest payment comes second - 42,9% and thirdly, the stereotypes and the feminist attitude of the society to this profession - 9,8%. Conclusion: From the analysis of the literary sources, it is clear that men have a long and significant connection with the provision of healthcare, but historically this is poorly documented. Over time this phenomenon underwent its metamorphosis under the influence of various factors. It is the time, when a decent place for men and women in the same-sex female nature of the nursing profession is assigned.